Comparative Study on Losses during Primary Processing of Bamboo and Low Girth Timber Logs - Gupta, Sachin; Lalmuankima, H. T.; Kishan Kumar, V. S. (Indian Forester, 2008)
In the present study, Poplar (Populus deltoides) logs and bamboo culms of Dendrocalamus giganteus ranging from 5 to 15 cm in diameter were taken and plane sawn in case of timber and split in case of bamboo to compare the consequent losses or wastage during the primary processing. It is found that there is a major difference in wastage in the primary processing as the losses/wastage in round wood varied from 60 to 65% whereas in the case of bamboo strips it remained below 5%. This situation deems to have a re-look at the use of wood as strips where strength of the strips is not of primary concern.